Eosinophilic oesophagitis: improving diagnosis and therapy – reducing the burden of repeated endoscopy. Issue Volume 13:Issue e1(2022) (2nd June 2022) - Dhar, Anjan; Haboubi, Hasan; Auth, Marcus; Attwood, Stephen
Abstract : Eosinophilic oesophagitis is now being diagnosed more often, although there continues to be a significant delay in the recognition of the condition in primary care, and among patients presenting with food bolus obstruction to other specialities like Ears, Nose and Throat and Accident & Emergency. The diagnosis requires endoscopy and biopsy, with six biopsies taken from at least two different areas of the oesophagus. The diagnostic threshold is > 15 eosinophils/high power field or 0.3 mm 2 . Dietary management although effective is often difficult to carry out due to poor adherence by patients and the need for a specialist dietitian and repeated biopsies. Orodispersible budesonide is very effective for inducing remission and maintaining it long term, with fewer biopsies. Newer targeted biological agents are promising in the treatment of patients who have not responded to conventional treatments. Dilatation of strictures in this condition is safe.